Marketing Influences on Perceptions of Reduced Nicotine Content Cigarettes. (23rd December 2019) - Johnson, Andrea C; Mays, Darren; Villanti, Andrea C; Niaura, Raymond S; Rehberg, Kathryn; Phan, Lilianna; Mercincavage, Melissa; Luta, George; Strasser, Andrew A
Abstract: Introduction: The Food and Drug Administration announced intent to reduce the nicotine content in cigarettes. There is limited evidence on how reduced nicotine content cigarette (RNC) marketing affects product beliefs and use, and research on this is needed to inform regulations. Methods: In an online experiment, 426 young adult cigarette smokers (aged 18–30 years) were randomized in a 2 (implicit: red package vs. blue package) × 2 (explicit: corrective message vs. no corrective message) design to view an advertisement for previously commercially available RNCs. Outcomes were advertisement content recall, product beliefs, and use intentions. Participants' responses to open-ended assessment of their beliefs about the stimuli were coded to identify prevailing themes. Results: Red packaging and corrective messaging were independently associated with greater advertisement content recall ( p = .01 and p = .04, respectively). There were no significant main or interaction effects on product beliefs or use intentions. Controlling for condition, advertisement content recall was significantly associated with less favorable product beliefs ( p < .001) and favorable product beliefs were associated with intent to use the product ( p < .001). Open-ended responses converged on the finding that respondents were interested in RNCs, but expressed skepticism about effectiveness and value. Conclusions: Brief exposure to an RNC advertisement with red packaging and corrective messaging were each independently associated with greater advertisement content recall. The results indicate: (1) interest and confusion among young adult smokers regarding RNCs, (2) beliefs about RNCs are influenced by marketing, and (3) beliefs are associated with intention to use RNCs. Implications: Findings from this study demonstrate the importance of advertising effects on beliefs about RNC products and support the need to regulate advertising and labeling alongside product regulation. More detailed study of advertisement features that affect consumers' beliefs about RNCs and how they impact their processing of explicit messaging about product risks will be important to guide regulatory decision-making.